Bioremediation of Selenium Contaminated Wastewater - van Hullebusch, Eric D. (Springer International Publishing : Imprint: Springer, 2017)
This book features the reduction and removal of selenium in wastewater via bioremediation. Arranged over five chapters, this book provides information regarding the interaction between micro-organisms and selenium, and it also explains the biogeochemistry of selenium in engineered ecosystems designed for wastewater treatment. The analytical approaches currently adopted by the scientific community are also described and discussed. Readers will find examples of the biological treatment of selenium contaminated wastewater, and discover a concise overview of selenium removal processes that are currently implemented at lab-scale as well as at industrial scale.
Keywords: Chemistry.; Analytical chemistry.; Biochemical engineering.; Microbiology.; Environmental engineering.; Biotechnology.; Water pollution.; elektronické knihy; electronic books